2018
DOI: 10.1002/2017ja024703
|View full text |Cite
|
Sign up to set email alerts
|

On the Nocturnal Downward and Westward Equatorial Ionospheric Plasma Drifts During the 17 March 2015 Geomagnetic Storm

Abstract: During quiet period, the nocturnal equatorial ionospheric plasma drifts eastward in the zonal direction and downward in the vertical direction. This quiet time drift pattern could be understood through dynamo processes in the nighttime equatorial ionosphere. The present case study reports the nocturnal simultaneous occurrence of the vertically downward and zonally westward plasma drifts over the Indian latitudes during the geomagnetic storm of 17 March 2015. After ~17:00 UT (~22:10 local time), the vertical pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…But, the same may not be applicable to other regions, so unlike Bagiya et al. (2018), we avoid using the hypothesis of Abdu et al. (1998) to explain the observed effect.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…But, the same may not be applicable to other regions, so unlike Bagiya et al. (2018), we avoid using the hypothesis of Abdu et al. (1998) to explain the observed effect.…”
Section: Discussionmentioning
confidence: 94%
“…Bagiya et al. (2018) have shown that the zonal drift of the irregularities in the Indian sector on the night of 17 March fluctuated from initial eastward to westward (at ∼1630 UT) and again eastward at ∼18 UT, eventually varying at small westward amplitude till 21 UT.…”
Section: Discussionmentioning
confidence: 99%
“…6.5°N) show westward drift of irregularity after 21:45 IST (IST = Indian Standard Time = UTC + 5:30 Hr), on 17 March 2015 (Patra et al., 2016). Observation from spaced GNSS receivers, located in Tirunelveli (8.73°N, 77.70°E; mag.0.32°N), show reversal of zonal irregularity drift during 16:30–18:00 UT (22:00–23:30 IST) of 17 March 2015 (Bagiya et al., 2018). Considering a westward drift was reported from 77°E (Tirunelveli) at 22:00 IST and from 79°E (Gadanki) at 21:45 IST, it can be conjectured to have reached Calcutta (88°E) at an earlier time.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the previous studies have reported presence of westward electric field during day-time of a geomagnetic disturbed period, leading to reduction in eastward electric field and hence inhibition in the height of Equatorial Ionization Anomaly (EIA) and h m F 2 , which was restricted over a limited longitude sector (Taiwan) BISWAS AND PAUL 10.1029/2023RS007669 4 of 16 (Kalita et al, 2016;Nayak et al, 2017;Rajesh et al, 2017). Ample previous studies have also reported reversal of night-time irregularity drift in the equatorial region, during an intense geomagnetic storm (Bagiya et al, 2018;de Paula et al, 2019;Kader et al, 2022;Patra et al, 2016). Therefore, in this study, efforts have also been made to investigate the effect of westward drifting irregularity, occurring during a geomagnetically disturbed day, on signal loss-of-lock when the zonal velocity component of the satellite was also westward.…”
Section: Biswas and Paulmentioning
confidence: 95%
“…Most of the studies on ionospheric response to solar flares pertain to periods during which either the effects of geomagnetic storms were not yet prevailed or the flare events were not accompanied by geomagnetic storms. The effects of geomagnetic storms over low-latitude ionosphere can be understood through electrodynamic (penetration of storm induced electric fields) and neutral dynamic (storm induced thermospheric neutral composition changes) coupling between high and low latitude ionosphere (e.g., Bagiya et al, 2011Bagiya et al, , 2014Bagiya et al, , 2018Blanc & Richmond, 1980;Fejer et al, 1983;Kelley et al, 2003;Nishida, 1968;Prolss, 1997;Tsurutani et al, 2004, and references therein). Both the flare and storm induced ionospheric changes vary with the local time (e.g., Bagiya et al, 2011;Chakrabarty et al, 2013).…”
Section: Introductionmentioning
confidence: 99%